Managing the complexities of the article-based future - Fund, Sven (Septentrio Conference Series, 2022)
Open access has created a new, complex reality for researchers, funders, librarians and publishers alike. Not only did the volume of items that need attention go up for many in the ecosystem. The broad variety of approaches and business models, alongside a whole new group of players, such as pure OA publishers, involved have driven up complexity. Virtually all elements of the publishing value chain – authorship, reviewing, curation, production, distribution, consumption and analytics – are effected by the change of the genetic code of the value chain. The impact on the different roles as well as on the value creation can be significant, depending on how the reconfiguration of publishing will evolve. The poster will look at ways in which the different players in the eco system can bring back efficiency while maintaining the openness to experimentation that is a vital part of Open Science. Stakeholders from all parts of the ecosystem are invited to join the conversation.